Microstructure changing and moisture removing of lychee during microwave vacuum drying - Luelue, Huang; Fang, Qiao; Daming, Fan (International Journal of Agricultural and Biological Engineering, 2016)
Micrographs of lychee pericarp and pulp during microwave vacuum drying were tested and analyzed in order to illuminate the microstructure change of lychee and effect of the change on moisture removing in lychee. The results showed that the pericarp consisted of three parts: outer layer with cuticle, inter layer and inner layer. Outer layer and inter layer cells are easily destroyed than inner layer because of small and intact inner layer cells. Furthermore, micrographs showed that the moisture content of pulp keep constant with the temperature increasing at first 40 min due to the inner layer cells prevent the moisture removing from pulp. The long tubular structure of pulp cell would become break and lost over time, because the intercellular spaces reduced and the moisture removing was slow down in pulp. Meanwhile, the microstructure of lychee dried with temperature control was better than that without temperature control. Keywords: Lychee, microstructure, microwave vacuum drying, moisture removal, temperature profile DOI: 10.3965/j.ijabe.20160903.1752 Citation: Huang L L, Qiao F, Fan D M. Microstructure changing and moisture removing of lychee during microwave vacuum drying. Int J Agric & Biol Eng, 2016; 9(3): 162－169.